Impact of Sewage Discharge on The Community Structure and Gonad Maturity of Fish in The Way Awi River Bandar Lampung - Sa'diah, Annisa Nurul; Tugiyono, Tugiyono; Suratman Umar; Gregorius Nugroho Susanto (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Water pollution refers to the introduction of living organisms, substances, or other components by human activities that can degrade water quality or cause environmental harm. Gonad maturity level indicates the stage of readiness of prospective broodstock for the spawning process, assessed through visual and histological methods. This study aimed to assess water quality in the Way Awi River based on fish community structure and to evaluate the impact of sewage discharge on fish gonad maturity levels in Bandar Lampung's Way Awi River. Conducted between November and December 2023, this research sampled five points along the Way Awi River. Chemical analysis included pH, BOD, COD, and DO, while physical parameters such as temperature and TSS (Total Suspended Solids) were also analyzed. The findings indicate that the Way Awi River is moderately polluted, with no significant impact on the community structure, although there is a noticeable decrease in fish numbers from upstream to downstream. This study underscores the importance of understanding the risks associated with continuous disposal of waste into rivers.